Subacute lung injury and biological exposure monitoring after repeated intratracheal administration of cadmium nitrate in rats - Hayashi, Emi; Dote, Tomotaro; Imanishi, Masafumi; Nakayama, Shin; Ohnishi, Keiko; Tsuji, Hiroshi; Usuda, Kan; Kono, Koichi (Biomedical Research on Trace Elements, 2010)
Recent increase in the use of cadmium nitrate Cd (NO3)2 (CdN) in nickel cadmium batteries means that workers at factories producing these batteries are at risk of frequent inhalation of CdN aerosols. We aimed to investigate the subacute harmful effects towards the lungs, liver, and kidneys after intermittent inhalation and biological monitoring of cadmium (Cd). Three doses of CdN and saline (control) were intratracheally administered to rats ten times during three weeks using an aerosol generator. Blood, bronchoalveolar lavage fluid (BALF), and lung tissues were sampled. Blood parameters indicated severe hypoxemia. Pathohistological findings of the CdN group indicated typical, though non-specific changes such as tissue-destructive processes, occupation of the alveolar region, proliferation-associated changes, and extensive deformities of alveolar architecture. Increased LDH and surfactant protein-D in BALF were suspected to be due to injurious effects and hyperplasia of the type- II pneumocytes. Blood Cd concentrations and BALF suggest that the absorbed dose was much lower than that of fatal cases following acute inhalation accidents. In a previous study, we defined serum levels of Cd at which no mortality and no abnormalities in the liver and kidneys were observed. However, it is generally reported that toxicity to the respiratory system is proportional to the time and level of exposure. Thus, subacute lethal effects were suspected to increase despite the minimal dose used in the present study, as repeated inhalation exposure and length of contact with Cd would yield severe pathohistological changes. Morphological abnormalities could also be responsible for the significant decrease in arterial blood gas values in this study. The marked pathologic change in the lungs, diagnosed as diffuse alveolar damage, was likely caused by repeated inhalation exposure of Cd. Subacute lung damage which worsened for a few days was lethal.